IMPLEMENTING MEDIA OF COMPUTER-BASED TEST FOR ENGLISH LANGUAGE PROFICIENCY OF VOCATIONAL HIGH SCHOOL STUDENTS AT THE BORDERLINE BETWEEN INDONESIA AND TIMOR LESTE - Balan, Yohanes Adio; Djuniadi, Djuniadi (Smart Comp :Jurnalnya Orang Pintar Komputer, 2016)
Research about â€œImplementing Media of Computer-Based Test for English LanguageProficiency of West Timorese Vocational High School Studentsâ€ is aimed to answer the question whetheror not the use of computer-based test effective and practical as the models of test instrument for Englishlanguage proficiency test of vocational high school students. It is a research and development (R and D)referred to Borg and Gall model (1989). The research took place at the borderline between Indonesia andTimor Leste, which covers three vocational high schools: SMKN 1 Kefamenanu, SMK KatolikKefamenanu and SMK Intan Grafika Kefamenanu. Software of Wonder share Quiz creator is used toproduce a model of computer-based test. The questions are chosen from standardized questions ofnational examination based on competency standard of the second grade students of SMK. Each singlequestion appears on computer screen, and the students are to answer by doing a click on the correctoptions. Validation was done to measure the quality of the computer-based test media, the effectivenessand the practicability of the CBT. The products and instruments are validated by expertise valuator oflecturers and teachers. The first validation came up with an unsatisfactory result, in which the indicatorshad not met the criteria or standards. After the revision, the second validations was conducted, theindicators had met the criteria or standards. The media of computer-based test and the practicability of theCBT are Valid.Key words: Computer-Based Test; E-learning; English proficiency